Coenzyme Q10 partially restores pathological alterations in a macrophage model of Gaucher disease - Mata, Mario de la (2017)
Background Gaucher disease (GD) is caused by mutations in the GBA1 gene which encodes lysosomal β-glucocerebrosidase (GCase). In GD, partial or complete loss of GCase activity causes the accumulation of the glycolipids glucosylceramide (GlcCer) and glucosylsphingosine in the lysosomes of macrophages. In this manuscript, we investigated the effects of glycolipids accumulation on lysosomal and mitochondrial function, inflammasome activation and efferocytosis capacity in a THP-1 macrophage model of Gaucher disease. In addition, the beneficial effects of coenzyme Q10 (CoQ) supplementation on cellular alterations were evaluated. Chemically-induced Gaucher macrophages were developed by differentiateing THP-1 monocytes to macrophages by treatment with phorbol 12-myristate 13-acetate (PMA) and then inhibiting intracellular GCase with conduritol B-epoxide (CBE), a specific irreversible inhibitor of GCase activity, and supplementing the medium with exogenous GlcCer. This cell model accumulated up to 16-fold more GlcCer compared with control THP-1 cells. Results Chemically-induced Gaucher macrophages showed impaired autophagy flux associated with mitochondrial dysfunction and increased oxidative stress, inflammasome activation and impaired efferocytosis. All abnormalities were partially restored by supplementation with CoQ. Conclusion These data suggest that targeting mitochondria function and oxidative stress by CoQ can ameliorate the pathological phenotype of Gaucher cells. Chemically-induced Gaucher macrophages provide cellular models that can be used to investigate disease pathogenesis and explore new therapeutics for GD.